Genome-Wide Identification of Aldehyde Oxidase Genes in Moths and Butterflies Suggests New Insights Into Their Function as Odorant-Degrading Enzymes - Godoy, Ricardo; Mutis, Ana; Carabajal Paladino, Leonela; Venthur, Herbert (Frontiers in Ecology and Evolution, 2022)
Aldehyde oxidases (AOXs) are common detoxifying enzymes in several organisms. In insects, AOXs act in xenobiotic metabolism and as odorant-degrading enzymes (ODEs). These last appear as crucial enzymes in the life cycle of insects, helping to reset their olfactory system, particularly in lepidopterans, which fulfill important ecological roles (e.g., pollination or destructive life cycles). A comprehensive understanding of their olfactory system has provided opportunities to study key chemosensory proteins. However, no significant advance has been made around lepidopteran AOXs research, and even less around butterflies, a recently evolved lineage. In this study we have identified novel AOX gene families in moths and butterflies in order to understand their role as ODEs. Eighteen genomes from both moths and butterflies were used for phylogenetics, molecular evolution and sequence analyses. We identified 164 AOXs, from which 91 are new. Their phylogeny showed two main clades that are potentially related to odorant-degrading function, where both moths and butterflies have AOXs. A first ODE-related clade seems to have a non-ditrysian origin, likely related to plant volatiles. A second ODE-related clade could be more pheromone-biased. Molecular evolution analysis suggests a slight purifying selection process, though a number of sites appeared under positive selection. ODE-related AOXs have changed a phenylalanine residue by proline in the active site. Finally, this study could serve as a reference for further evolutionary and functional studies around Lepidopteran AOXs.